2020
DOI: 10.3390/ijerph17238889
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Spheno-Occipital Synchondrosis Ossification in Children and Adolescents with Cleft Lip and Palate: A Retrospective Case-Control Study

Abstract: Background: Cleft lip and palate (CLP) can affect the development of the maxilla; which may create a midfacial deficiency as well as an interference of the facial growth pattern and dentofacial esthetics. Objective: This study aimed to estimate the chronological age of complete fusion of the spheno-occipital synchondrosis (SOS) in cleft lip and palate patients and a control group; using cone beam computed tomography (CBCT) images. Methods: In this retrospective study; 125 patients were enrolled (cleft lip and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…So, the obtained results were in line with the results of the previous studies, which showed earlier ossification in females than males. [22][23][24][25][26][27][28][29] Despite these similarities, there are some differences in the results. In a study on the normal Australian population, the average age of complete SOS fusion for both females and males was 18.62 years and 19.83 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…So, the obtained results were in line with the results of the previous studies, which showed earlier ossification in females than males. [22][23][24][25][26][27][28][29] Despite these similarities, there are some differences in the results. In a study on the normal Australian population, the average age of complete SOS fusion for both females and males was 18.62 years and 19.83 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The most preferred diagnostic tool prior to orthodontic treatment was cone beam computed tomography (CBCT). Despite the Eurocleft study using lateral cephalograms, CBCT has become a diagnostic imaging tool in patients with CLP since it had a higher definition than conventional two-dimensional methods and lower radiation exposure compared with computed tomography [ 22 , 23 ]. The American Academy of Oral and Maxillofacial Radiology defined clinical recommendations regarding the use of CBCT and this included imaging in the context of CLP care, since these patients have medical conditions that required proper 3D analysis for accurate diagnosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include skeletal abnormalities, such as abnormal development of the maxillary bones, frontal, zygomatic, and orbital bones, as reported in a study conducted in Taiwan [6]. However, it is noteworthy that there was no statistical difference in the ossification time of the Spheno-Occipital Synchondrosis in patients with UCLP compared to patients without cleft [7].…”
Section: Introductionmentioning
confidence: 86%